Preparation method of anti-aging modified asphalt waterproof coiled material
By preparing a modified asphalt matrix containing an anti-aging agent and a waterproof functional agent and combining it with the tire base layer, the aging problem of the modified asphalt waterproof membrane is solved and the anti-aging and waterproof properties of the material are improved.
Patent Information
- Application Number
- CN202511068575.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-10-10
- Estimated Expiration
- 2045-07-31
AI Technical Summary
Existing modified asphalt waterproof membranes have poor antioxidant properties and compatibility issues, which lead to rapid aging of the material, reduced flexibility and adhesion, and increased risk of water seepage.
Polyethylene film, tread base and modified asphalt matrix are used. The modified asphalt matrix is composed of asphalt, SBS elastomer, softener, waterproof functional agent, anti-aging agent and composite filler. The modified asphalt matrix is prepared by mixing at a specific temperature and time, and coated on the tread base. Finally, it is covered with polyethylene film for isolation to form an aging-resistant modified asphalt waterproof membrane.
It improves the anti-aging performance of asphalt, enhances the mechanical properties and waterproofness of the matrix, and improves the high temperature aging resistance and waterproof performance of the material.
Smart Images

Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof coiled materials, in particular to a method for preparing an aging-resistant modified asphalt waterproof coiled material. Background Art
[0002] Currently, the production of modified asphalt waterproofing membranes primarily relies on high-quality road asphalt as the base material, while waste motor oil and rubber oil are used as softeners, physically combined with polymer modifiers. Furthermore, jute, fiberglass mats, and polyester non-woven fabrics are used as the base material, and a silicone-based release film or paper is applied as a removable release layer to complete the production process.
[0003] The addition of high-molecular-weight polymers helps improve asphalt's low-temperature performance and heat resistance, thereby modulating the temperature sensitivity of asphalt coatings. However, due to asphalt's inherently poor oxidation resistance and compatibility issues with polymers, rapid aging and phase separation can occur. This reduces the waterproofing membrane's flexibility and adhesion, increasing the risk of water seepage.
[0004] In response to the above-mentioned problems, the present invention provides a method for preparing an aging-resistant modified asphalt waterproof membrane, which can solve the problems existing in the prior art. Summary of the Invention
[0005] The purpose of the present invention is to provide a method for preparing an aging-resistant modified asphalt waterproofing membrane.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] An aging-resistant modified asphalt waterproofing membrane, characterized by comprising a polyethylene film, a base layer, and a modified asphalt matrix;
[0008] The modified asphalt matrix comprises the following components in parts by weight: 45-60 parts of asphalt, 10-15 parts of styrene-butadiene-styrene triblock copolymer (SBS) elastomer, 8-12 parts of softener, 3-5 parts of waterproofing agent, 4-6 parts of anti-aging agent, 5-9 parts of SBR, 5-10 parts of composite filler, and 0.03-0.05 parts of initiator.
[0009] The modified asphalt matrix preparation method comprises the following steps:
[0010] Step 1: Mixing asphalt and a softener at 100-110° C. to prepare a mixture β;
[0011] Step 2: Mixture β and SBS elastomer are mixed at 130-160° C. for 1-2 hours, and then SBR, waterproof functional agent, anti-aging agent, and initiator are added and mixed for 1-3 hours to obtain mixture β1;
[0012] Step 3: Mix the mixture β1 with 5-10 parts of the composite filler at 160-180° C. for 1-2 hours to prepare a modified asphalt matrix.
[0013] Furthermore, the tire base layer is any one of polyester fiber non-woven fabric and glass fiber felt.
[0014] Furthermore, the softener is any one of butyl oleate, trioctyl citrate, cashew nut shell oil, and naphthenic oil; the SBS elastomer is any one of SBS-g-GMA, SBS-g-MAH, and star-shaped SBS; and the asphalt is any one of 200# asphalt, 90# asphalt, and 70# asphalt.
[0015] Furthermore, the composite filler is a mixture of kaolin and heavy calcium carbonate in a mass ratio of 1:1; and the SBR is 85-98wt% of solution-polymerized styrene-butadiene rubber.
[0016] Furthermore, the preparation method of the anti-aging agent comprises the following steps:
[0017] Step A1: Add 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid to trichloroethane, slowly add thionyl chloride, raise the temperature to 50-55°C, react for 6-8 hours under anaerobic conditions, and distill under reduced pressure to obtain intermediate a. The reaction route is:
[0018] ;
[0019] Step A2: Add 3-amino-4-chlorotrifluoromethoxybenzene and intermediate a to dichloromethane, then add triethylamine, react for 2-3 hours under ice-water bath, extract, wash, and dry to obtain intermediate b. The reaction route is:
[0020] ;
[0021] Step A3: Add 1,2,2,6,6-pentamethylpiperidinol and intermediate b to dimethyl sulfoxide, stir and dissolve at 55-65°C, add alkaline solution, stir for 8-10 hours, extract, wash, and dry to obtain an anti-aging agent. The reaction route is:
[0022] ;
[0023] In the above technical scheme, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid is chloromethylated to obtain intermediate a, 3-amino-4-chlorotrifluoromethoxybenzene is reacted with intermediate a to obtain fluorine-containing intermediate b, and 1,2,2,6,6-pentamethylpiperidinol is grafted onto intermediate b through a substitution reaction between alcoholic hydroxyl groups and halogen atoms to obtain an anti-aging agent.
[0024] Furthermore, in step A1, the ratio of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid to thionyl chloride is 1 g:1.4-1.6 mL.
[0025] Furthermore, in step A2, the mass ratio of the 3-amino-4-chlorotrifluoromethoxybenzene to the intermediate a is 1:0.8-1.2; in step A3, the mass ratio of the 1,2,2,6,6-pentamethylpiperidinol to the intermediate b is 1:3-3.5; and the alkaline solution is a 30% by mass sodium hydroxide aqueous solution.
[0026] Furthermore, the method for preparing the waterproof functional agent comprises the following steps:
[0027] Step S1: Ultrasonic dispersion of nano-calcium carbonate in anhydrous ethanol solution for 1-2 hours, heating to 80° C., dropwise addition of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and reacting for 2-3 hours, removing the solvent, and drying the powder in a vacuum oven at 110-120° C. for 2-4 hours to obtain modified nano-calcium carbonate;
[0028] Step S2: adding isophytol and 2-aminoterephthalic acid to benzene, then adding thionyl chloride, stirring for 5-10 minutes, ultrasonically reacting at 70-80° C. for 16-24 hours, adding petroleum ether, filtering, then adjusting the pH to 7-8 with cooled saturated sodium carbonate solution, filtering, washing, and drying to obtain intermediate 1;
[0029] Step S3: adding intermediate 1 to toluene, adjusting the pH to 8-8.5, heating to 60-80° C., slowly adding modified nano-calcium carbonate and triethylamine, stirring under nitrogen protection, reacting for 6-8 hours, filtering, washing, and drying to obtain a waterproof functional agent.
[0030] In the above technical solution, modified nano-calcium carbonate containing epoxy groups is obtained by modifying nano-calcium carbonate with a silane coupling agent, and then the hydroxyl group of isophytol is esterified with the carboxylic acid group of 2-aminoterephthalic acid to obtain an intermediate 1 containing an amino group. The epoxy group and the amino group undergo a ring-opening reaction under the catalysis of toluene to obtain a waterproof functional agent containing an unsaturated long chain.
[0031] Furthermore, in step S1, the usage ratio of the nano-calcium carbonate and 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 1g:0.008-0.01mol; in step S2, the mass ratio of the isophytol and 2-aminoterephthalic acid is 1:0.3-0.5; in step S3, the solvent is any one of isopropanol and toluene.
[0032] A method for preparing an aging-resistant modified asphalt waterproof membrane comprises the following steps:
[0033] Step 1: Heat the modified asphalt base to 130-160°C, apply it on both sides of the base layer, and perform hot pressing to prepare an aging-resistant modified asphalt waterproof membrane intermediate;
[0034] Step 2: Cover and isolate both sides of the intermediate body of the aging-resistant modified asphalt waterproofing membrane with polyethylene film, compact, cool, and roll up to obtain the aging-resistant modified asphalt waterproofing membrane.
[0035] Beneficial effects of the present invention:
[0036] (1) The present invention prepares an anti-aging agent containing hindered amines, hindered phenols, and fluorine-containing groups, wherein the piperidine amine group contained in the structure of the hindered amine light stabilizer will first be converted into a stable nitrogen oxide free radical, and then capture the active free radicals generated in the polymer, and the chain reaction is terminated, thereby enhancing the anti-aging performance of asphalt. At the same time, the hindered phenol also contains a substituted hydroxyl group and its aromatic structure, which can also scavenge free radicals, thereby playing a synergistic antioxidant role. The anti-aging agent also has a benzene ring rigid structure that can improve the mechanical properties of the matrix, and the fluorine-containing group can improve the hydrophobicity of the matrix and give the matrix waterproofness.
[0037] (2) The present invention improves the defect of easy agglomeration of nanomaterials in the matrix by organically modifying nano calcium carbonate to prepare a waterproof functional agent. At the same time, the nano calcium carbonate itself can cooperate with unsaturated long-chain olefins and aromatic rings and benzene rings in antioxidants to improve the high-temperature aging resistance of the matrix. The unsaturated long-chain olefins can also enhance the water resistance and waterproof performance of the matrix with the fluorine-containing functional groups in the antioxidant. The large number of unsaturated long chains grafted by nano calcium carbonate can improve the density of the matrix, and can form a cross-linked structure with the antioxidant and the unsaturated double bonds in the matrix through an initiator to form a complex network structure, giving the matrix excellent mechanical properties.
[0038] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. DETAILED DESCRIPTION
[0039] The following describes preferred embodiments of the present invention. It should be understood that the embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention.
[0040] Preparation Example 1
[0041] The method for preparing the anti-aging agent comprises the following steps:
[0042] Step A1: Add 3 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid to 40 ml of trichloroethane, slowly add 4.2 ml of thionyl chloride, raise the temperature to 50°C, react for 6 hours under anaerobic conditions, and distill under reduced pressure to obtain intermediate a;
[0043] Step A2: 2 g of 3-amino-4-chlorotrifluoromethoxybenzene and 1.6 g of intermediate a were added to 30 ml of dichloromethane, followed by 0.03 mol of triethylamine. The mixture was reacted for 2 h in an ice-water bath, and then extracted, washed, and dried to obtain intermediate b.
[0044] Step A3: Add 1.2 g of 1,2,2,6,6-pentamethylpiperidinol and 3.6 g of intermediate b to 30 ml of dimethyl sulfoxide, stir and dissolve at 55°C, add 0.8 g of alkaline solution, stir for 8 hours, extract, wash, and dry to obtain an anti-aging agent.
[0045] The method for preparing the waterproof functional agent comprises the following steps:
[0046] Step S1: 1.5 g of nano-calcium carbonate was ultrasonically dispersed in 30 ml of anhydrous ethanol solution for 1 h, heated to 80° C., 2.8 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise and stirred for 2 h, the solvent was removed, and the powder was dried in a vacuum oven at 110° C. for 2 h to obtain modified nano-calcium carbonate;
[0047] Step S2: 3 g of isophytol and 1 g of 2-aminoterephthalic acid were added to a container, followed by 0.03 g of thionyl chloride, stirred for 5 min, and ultrasonically reacted at 70° C. for 16 h. Petroleum ether was added, the mixture was filtered, and the pH value was adjusted to 7 using a cooled saturated sodium carbonate solution. The mixture was filtered, washed, and dried to obtain Intermediate 1.
[0048] Step S3: Add 3.2 g of intermediate 1 to 30 ml of toluene solvent, adjust the pH to 8, heat to 60° C., slowly add 2.1 g of modified nano-calcium carbonate and 1.8 ml of triethylamine, stir and react for 6 h under nitrogen protection, filter, wash, and dry to obtain a waterproof functional agent.
[0049] For the loss on ignition test, weigh a crucible (M1), add 5g of a waterproofing agent, and weigh the crucible containing the sample to obtain M2. The crucible containing the sample is then calcined in a muffle furnace at 500°C for 5 hours. Remove the crucible, cool it to room temperature in a desiccator, and weigh it to obtain M3. The mass percentage of the loss on ignition (X) is calculated using the formula X = (M2-M3) / (M2-M1) × 100%. The test result shows a loss on ignition of 45.4%. The loss on ignition is primarily composed of organic long alkanes grafted onto the surface of the nano-calcium carbonate and a very small amount of water.
[0050] Preparation Example 2
[0051] The method for preparing the anti-aging agent comprises the following steps:
[0052] Step A1: 3g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid was added to 40ml of trichloroethane, 4.5ml of dichloro sulfoxide was added slowly, the temperature was raised to 53℃, the reaction was carried out for 6.5h under oxygen-free condition, and the intermediate a was prepared after distillation under reduced pressure;
[0053] Step A2: 2g of 3-amino-4-chlorotrifluoromethoxybenzene and 2.1g of intermediate a were added to 30ml of dichloromethane, 0.03mol of triethylamine was added, the reaction was carried out for 2.5h under ice water bath, extraction, washing, and drying to prepare intermediate b;
[0054] Step A3: 1.2g of 1,2,2,6,6-pentamethylpiperidinol and 4g of intermediate b were added to 30ml of dimethyl sulfoxide, the solution was stirred and dissolved at 60℃, 0.8g of alkali solution was added, stirring was carried out for 9h, extraction, washing, drying, and the anti-aging agent was prepared.
[0055] The preparation method of the waterproof functional agent comprises the following steps:
[0056] Step S1: 1.5g of nano calcium carbonate was ultrasonically dispersed in 30ml of anhydrous ethanol solution for 1h, heated to 80℃, 3.2g of 3-(2,3-epoxypropoxy)propyl trimethoxysilane was added dropwise, and stirring was carried out for 3h, then the solvent was removed, and the powder was dried in a vacuum oven at 113℃ for 3h to prepare modified nano calcium carbonate;
[0057] Step S2: 3g of isofarnesol and 1.2g of 2-amino terephthalic acid were added to a container, 0.03g of dichloro sulfoxide was added, stirring was carried out for 8min, ultrasonic reaction was carried out for 20h at 75℃, petroleum ether was added, filtration was carried out, then a cooling saturated sodium carbonate solution was used to adjust the pH value to 7.5, filtration was carried out, washing was carried out, and drying was carried out to prepare intermediate 1;
[0058] Step S3: 3.2g of intermediate 1 was added to 30ml of solvent toluene, the pH value was adjusted to 8, the temperature was raised to 60℃, 2.5g of modified nano calcium carbonate and 1.8ml of triethylamine were slowly added, stirring was carried out for 6h under nitrogen protection, filtration was carried out, washing was carried out, drying was carried out, and the waterproof functional agent was prepared.
[0059] Loss on ignition test: the weight of the crucible was taken as M1, 5g of the waterproof functional agent was added to the crucible, the weight of the crucible containing the sample was taken as M2, then the crucible containing the sample was placed in a muffle furnace and calcined at 500℃ for 5h, the crucible was taken out and placed in a desiccator to cool to room temperature, and the weight was taken as M3. The mass percentage X of the loss on ignition was calculated according to the formula X=(M2-M3) / (M2-M1)×100%, and the test result was that the loss on ignition was 46.5%, and the loss on ignition components were basically organic long alkanes grafted on the surface of nano calcium carbonate and a small amount of water.
[0060] Preparation Example 3
[0061] The method for preparing the anti-aging agent comprises the following steps:
[0062] Step A1: Add 3 g of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid to 40 ml of trichloroethane, slowly add 4.5 ml of thionyl chloride, raise the temperature to 50°C, react under anaerobic conditions for 6.5 hours, and distill under reduced pressure to obtain intermediate a;
[0063] Step A2: 2 g of 3-amino-4-chlorotrifluoromethoxybenzene and 2.1 g of intermediate a were added to 30 ml of dichloromethane, followed by 0.03 mol of triethylamine. The mixture was reacted under ice-water bath for 2.5 h, extracted, washed, and dried to obtain intermediate b.
[0064] Step A3: Add 1.2 g of 1,2,2,6,6-pentamethylpiperidinol and 4 g of intermediate b to 30 ml of dimethyl sulfoxide, stir and dissolve at 60°C, add 0.8 g of alkaline solution, stir for 9 hours, extract, wash, and dry to obtain an anti-aging agent.
[0065] The method for preparing the waterproof functional agent comprises the following steps:
[0066] Step S1: 1.5 g of nano-calcium carbonate was ultrasonically dispersed in 30 ml of anhydrous ethanol solution for 1 h, heated to 80° C., 3.5 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise and stirred for 3 h, then the solvent was removed and the powder was dried in a vacuum oven at 120° C. for 4 h to obtain modified nano-calcium carbonate;
[0067] Step S2: 3 g of isophytol and 1.5 g of 2-aminoterephthalic acid were added to a container, followed by 0.03 g of thionyl chloride, stirred for 10 min, and ultrasonically reacted at 80° C. for 24 h. Petroleum ether was added, the mixture was filtered, and the pH value was adjusted to 8 using a cooled saturated sodium carbonate solution. The mixture was filtered, washed, and dried to obtain Intermediate 1.
[0068] Step S3: Add 3.2 g of intermediate 1 to 30 ml of toluene solvent, adjust the pH to 8, heat to 60° C., slowly add 3.2 g of modified nano-calcium carbonate and 1.8 ml of triethylamine, stir and react for 8 h under nitrogen protection, filter, wash, and dry to obtain a waterproof functional agent.
[0069] For the loss on ignition test, weigh a crucible (M1), add 5g of a waterproofing agent, and weigh the crucible containing the sample to obtain M2. The crucible containing the sample is then calcined in a muffle furnace at 500°C for 5 hours. Remove the crucible, cool it to room temperature in a desiccator, and weigh it to obtain M3. The mass percentage of the loss on ignition (X) is calculated using the formula X = (M2-M3) / (M2-M1) × 100%. The test result shows a loss on ignition of 45.8%. The loss on ignition is primarily composed of organic long alkanes grafted onto the surface of the nano-calcium carbonate and a very small amount of water.
[0070] Example 1
[0071] A method for preparing an aging-resistant modified asphalt waterproof membrane comprises the following steps:
[0072] Step 1: Heat the modified asphalt base to 130-160°C, apply it on both sides of the base layer, and perform hot pressing to prepare an aging-resistant modified asphalt waterproof membrane intermediate;
[0073] Step 2: Cover and isolate both sides of the intermediate body of the aging-resistant modified asphalt waterproofing membrane with polyethylene film, compact, cool, and roll up to obtain the aging-resistant modified asphalt waterproofing membrane.
[0074] The preparation method of the modified asphalt matrix comprises the following steps:
[0075] Step 1: Mixing 45 parts of asphalt and 8 parts of softener at 100° C. to prepare a mixture β;
[0076] Step 2: Mixture β and 10 parts of SBS elastomer, by weight, were mixed at 130° C. for 1 hour, followed by the addition of 5 parts of SBR, 3 parts of a waterproofing agent, 4 parts of an anti-aging agent, and 0.03 parts of an initiator, and the mixture was mixed for 1 hour to obtain mixture β1;
[0077] Step 3: Mix the mixture β1 with 5 parts of the composite filler by weight at 160° C. for 1 hour to prepare a modified asphalt matrix.
[0078] The anti-aging functional agent and waterproof functional agent are the same as those in Preparation Example 2.
[0079] Example 2
[0080] A method for preparing an aging-resistant modified asphalt waterproof membrane comprises the following steps:
[0081] Step 1: Heat the modified asphalt base to 148°C, apply it to both sides of the base layer, and perform hot pressing to prepare an aging-resistant modified asphalt waterproof membrane intermediate;
[0082] Step two: the aging resistant modified asphalt waterproofing membrane intermediate is covered with polyethylene film on both sides, compacted, cooled, and rolled to obtain the aging resistant modified asphalt waterproofing membrane.
[0083] The preparation method of the modified asphalt base comprises the following steps:
[0084] Step 1: 50 parts of asphalt and 10 parts of softening agent are mixed at 103℃ to obtain a mixture β.
[0085] Step 2: 11 parts of SBS elastomer are mixed with the mixture β at 145℃ for 1-2h, then 7 parts of SBR, 4.8 parts of waterproof functional agent, 5.7 parts of anti-aging agent, and 0.04 parts of initiator are added and mixed for 2h to obtain a mixture β1.
[0086] Step 3: 6 parts of composite filler are mixed with the mixture β1 at 172℃ for 1.5h to obtain the modified asphalt base.
[0087] The anti-aging functional agent and the waterproof functional agent are the same as those in Preparation Example 2.
[0088] Example 3
[0089] A preparation method of an aging resistant modified asphalt waterproofing membrane comprises the following steps:
[0090] Step one: the modified asphalt base is heated to 160℃, coated on both sides of the base layer, and hot-pressed and shaped to obtain an aging resistant modified asphalt waterproofing membrane intermediate.
[0091] Step two: the aging resistant modified asphalt waterproofing membrane intermediate is covered with polyethylene film on both sides, compacted, cooled, and rolled to obtain the aging resistant modified asphalt waterproofing membrane.
[0092] The preparation method of the modified asphalt base comprises the following steps:
[0093] Step 1: 60 parts of asphalt and 12 parts of softening agent are mixed at 110℃ to obtain a mixture β.
[0094] Step 2: 15 parts of SBS elastomer are mixed with the mixture β at 160℃ for 2h, then 9 parts of SBR, 5 parts of waterproof functional agent, 6 parts of anti-aging agent, and 0.05 parts of initiator are added and mixed for 3h to obtain a mixture β1.
[0095] Step 3: 10 parts of composite filler are mixed with the mixture β1 at 180℃ for 2h to obtain the modified asphalt base.
[0096] The anti-aging functional agent and the waterproof functional agent are the same as those in Preparation Example 2.
[0097] Comparative Example 1
[0098] A method for preparing an aging-resistant modified asphalt waterproof membrane comprises the following steps:
[0099] Step 1: Heat the modified asphalt base to 148°C, apply it to both sides of the base layer, and perform hot pressing to prepare an aging-resistant modified asphalt waterproof membrane intermediate;
[0100] Step 2: Cover and isolate both sides of the intermediate body of the aging-resistant modified asphalt waterproofing membrane with polyethylene film, compact, cool, and roll up to obtain the aging-resistant modified asphalt waterproofing membrane.
[0101] The preparation method of the modified asphalt matrix comprises the following steps:
[0102] Step 1: Mixing 50 parts of asphalt and 10 parts of softener at 103° C. to prepare a mixture β;
[0103] Step 2: Mixture β and 11 parts of SBS elastomer, by weight, were mixed at 145° C. for 1-2 hours, followed by the addition of 7 parts of SBR, 5.7 parts of an anti-aging agent, and 0.04 parts of an initiator, and the mixture was mixed for 2 hours to obtain mixture β1;
[0104] Step 3: Mix the mixture β1 with 6 parts of the composite filler by weight at 172° C. for 1.5 hours to prepare a modified asphalt matrix.
[0105] The anti-aging functional agent is the same as that in Preparation Example 2.
[0106] Comparative Example 2
[0107] A method for preparing an aging-resistant modified asphalt waterproof membrane comprises the following steps:
[0108] Step 1: Heat the modified asphalt base to 148°C, apply it to both sides of the base layer, and perform hot pressing to prepare an aging-resistant modified asphalt waterproof membrane intermediate;
[0109] Step 2: Cover and isolate both sides of the intermediate body of the aging-resistant modified asphalt waterproofing membrane with polyethylene film, compact, cool, and roll up to obtain the aging-resistant modified asphalt waterproofing membrane.
[0110] The preparation method of the modified asphalt matrix comprises the following steps:
[0111] Step 1: Mixing 50 parts of asphalt and 10 parts of softener at 103° C. to prepare a mixture β;
[0112] Step 2: Mixture β and 11 parts of SBS elastomer, by weight, were mixed at 145° C. for 1-2 hours, followed by the addition of 7 parts of SBR, 4.8 parts of a waterproofing agent, and 0.04 parts of an initiator, and the mixture was mixed for 2 hours to obtain mixture β1.
[0113] Step 3: Mix the mixture β1 with 6 parts of the composite filler by weight at 172° C. for 1.5 hours to prepare a modified asphalt matrix.
[0114] The waterproof functional agent is the same as that in Preparation Example 2.
[0115] Comparative Example 3
[0116] A method for preparing an aging-resistant modified asphalt waterproof membrane comprises the following steps:
[0117] Step 1: Heat the modified asphalt base to 148°C, apply it to both sides of the base layer, and perform hot pressing to prepare an aging-resistant modified asphalt waterproof membrane intermediate;
[0118] Step 2: Cover and isolate both sides of the intermediate body of the aging-resistant modified asphalt waterproofing membrane with polyethylene film, compact, cool, and roll up to obtain the aging-resistant modified asphalt waterproofing membrane.
[0119] The preparation method of the modified asphalt matrix comprises the following steps:
[0120] Step 1: Mixing 50 parts of asphalt and 10 parts of softener at 103° C. to prepare a mixture β;
[0121] Step 2: Mixture β and 11 parts of SBS elastomer, by weight, were mixed at 145° C. for 1-2 hours, followed by the addition of 7 parts of SBR and 0.04 parts of initiator, and the mixture was mixed for 2 hours to obtain mixture β1;
[0122] Step 3: Mix the mixture β1 with 6 parts of the composite filler by weight at 172° C. for 1.5 hours to prepare a modified asphalt matrix.
[0123] Performance testing:
[0124] Thermal aging test: The modified asphalt matrix was subjected to thermal aging test in accordance with GB18242-2008 "Elastomer modified asphalt waterproof membrane" standard. (70±0.5) g of molten modified asphalt matrix was poured into an aging tray (φ150mm×9.5mm) and placed in a thermal aging chamber. The aging conditions were: 80°C, 10 days. UV aging test: The modified asphalt matrix was subjected to UV aging test in accordance with GB / T18244-2022 "Test method for aging of building waterproof materials". (70±0.5) g of molten modified asphalt matrix was poured into an aging tray (φ150mm×9.5mm) and placed in a UV aging chamber. The aging conditions were: UV light intensity 2000μW / cm 2 , 60℃, 10d; refer to the method specified in GB / T23457-2009 to test the anti-seepage performance of the waterproof membrane after the above treatment, pressurize the water-facing surface of the membrane to 0.2MPa and maintain for 4h, then increase the pressure by 0.1Mpa for 4h each time until the membrane seeps water, and observe the test pressure of water when the membrane seeps water; refer to the method specified in GB / T328.8-2007 to test the tensile properties of the membrane after the above treatment; refer to the method specified in GB / T328.9-2007 to perform a nail rod tear strength test on the modified asphalt matrix after the above treatment.
[0125] Table 1: Performance test results of the embodiment
[0126]
[0127] Table 2: Comparative performance test results
[0128]
[0129] It can be concluded from the table that, after thermal aging and UV aging, performance tests were conducted on Examples 1-3 of the present invention. Due to the addition of the prepared anti-aging agent and waterproof functional agent, the test results showed that all of them had excellent waterproof performance, anti-aging performance, and mechanical properties.
[0130] Comparative Example 1 did not add a waterproofing agent in the preparation of the modified asphalt matrix, so it did not have a large amount of unsaturated long-chain olefins and nano-calcium carbonate. Therefore, in the test, the initial mechanical properties were poor, the mechanical properties after thermal aging were also poor, the anti-ultraviolet aging performance was good, and the waterproofing performance was poor; Comparative Example 2 did not add an anti-aging agent in the preparation of the modified asphalt matrix, so after ultraviolet aging, various properties declined significantly and performed poorly; Comparative Example 3 did not add an anti-aging agent and a waterproofing agent in the preparation of the modified asphalt matrix, so it not only performed the worst in the initial mechanical properties test, but also performed even worse in the anti-aging performance, and the waterproofing performance was the worst among all the comparative examples.
[0131] The above content is merely an example and explanation of the concept of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.
Claims
1. An aging-resistant modified asphalt waterproof membrane, characterized by: It includes polyethylene film, tread base, and modified asphalt matrix; The modified asphalt matrix comprises the following components in parts by weight: 45-60 parts of asphalt, 10-15 parts of SBS elastomer, 8-12 parts of softener, 3-5 parts of waterproofing agent, 4-6 parts of anti-aging agent, 5-9 parts of SBR, 5-10 parts of composite filler, and 0.03-0.05 parts of initiator. The modified asphalt matrix preparation method comprises the following steps: Step 1: Mixing asphalt and a softener at 100-110° C. to prepare a mixture A; Step 2: Mixture A and SBS elastomer are mixed at 130-160° C. for 1-2 hours, and then SBR, waterproofing agent, anti-aging agent, and initiator are added and mixed for 1-3 hours to prepare mixture β; Step 3: Mixing the mixture β with the composite filler at 160-180° C. for 1-2 hours to prepare a modified asphalt matrix; The method for preparing the anti-aging agent comprises the following steps: Step A1: Add 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid to trichloroethane, slowly add thionyl chloride, raise the temperature to 50-55°C, react for 6-8 hours under anaerobic conditions, and distill under reduced pressure to obtain intermediate a; Step A2: Add 3-amino-4-chlorotrifluoromethoxybenzene and intermediate a to dichloromethane, then add triethylamine, react under ice-water bath for 2-3 hours, extract, wash, and dry to obtain intermediate b; Step A3: Add 1,2,2,6,6-pentamethylpiperidinol and intermediate b to dimethyl sulfoxide, stir and dissolve at 55-65° C., add alkaline solution, stir for 8-10 hours, extract, wash, and dry to obtain an anti-aging agent.
2. The aging-resistant modified asphalt waterproof membrane according to claim 1, characterized in that: The base layer is any one of polyester fiber non-woven fabric and glass fiber felt.
3. The aging-resistant modified asphalt waterproof membrane according to claim 1, characterized in that: The softener is any one of butyl oleate, trioctyl citrate, cashew nut shell oil, and naphthenic oil; the SBS elastomer is any one of SBS-g-GMA, SBS-g-MAH, and star-shaped SBS; and the asphalt is any one of 200# asphalt, 90# asphalt, and 70# asphalt.
4. The aging-resistant modified asphalt waterproof membrane according to claim 1, characterized in that: The composite filler is a mixture of kaolin and heavy calcium carbonate in a mass ratio of 1:1; and the SBR is 85-98wt% of solution-polymerized styrene-butadiene rubber.
5. The aging-resistant modified asphalt waterproof membrane according to claim 1, characterized in that: In step A1, the ratio of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid to thionyl chloride is 1 g: 1.4-1.6 mL.
6. The aging-resistant modified asphalt waterproof membrane according to claim 1, characterized in that: In step A2, the mass ratio of the 3-amino-4-chlorotrifluoromethoxybenzene to the intermediate a is 1:0.8-1.2; in step A3, the mass ratio of the 1,2,2,6,6-pentamethylpiperidinol to the intermediate b is 1:3-3.5; and the alkaline solution is a 30% by mass aqueous solution of sodium hydroxide.
7. The aging-resistant modified asphalt waterproof membrane according to claim 1, characterized in that: The method for preparing the waterproof functional agent comprises the following steps: Step S1: Ultrasonic dispersion of nano-calcium carbonate in anhydrous ethanol solution for 1-2 hours, heating to 80° C., dropwise addition of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring and reacting for 2-3 hours, removing the solvent, and drying the powder in a vacuum oven at 110-120° C. for 2-4 hours to obtain modified nano-calcium carbonate; Step S2: adding isophytol and 2-aminoterephthalic acid to a container, then adding thionyl chloride, stirring for 5-10 minutes, ultrasonically reacting at 70-80° C. for 16-24 hours, adding petroleum ether, filtering, then adjusting the pH to 7-8 with cooled saturated sodium carbonate solution, filtering, washing, and drying to obtain intermediate 1; Step S3: adding intermediate 1 to a solvent, adjusting the pH to 8-8.5, heating to 60-80° C., slowly adding modified nano-calcium carbonate and triethylamine, stirring under nitrogen protection, reacting for 6-8 hours, filtering, washing, and drying to obtain a waterproof functional agent.
8. The aging-resistant modified asphalt waterproof membrane according to claim 7, characterized in that: In step S1, the usage ratio of the nano-calcium carbonate and 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 1g:0.008-0.01mol; in step S2, the mass ratio of the isophytol and 2-aminoterephthalic acid is 1:0.3-0.5; in step S3, the solvent is any one of isopropanol and toluene; the mass ratio of the intermediate 1 to the modified nano-calcium carbonate is 1:0.6-1.
9. A method for preparing an aging-resistant modified asphalt waterproof membrane according to claim 1, comprising the following steps: Step 1: Heat the modified asphalt base to 130-160°C, apply it on both sides of the base layer, and perform hot pressing to prepare an aging-resistant modified asphalt waterproof membrane intermediate; Step 2: Cover and isolate both sides of the intermediate body of the aging-resistant modified asphalt waterproofing membrane with polyethylene film, compact, cool, and roll up to obtain the aging-resistant modified asphalt waterproofing membrane.
Citation Information
Patent Citations
Anti-aging elastomer-modified asphalt waterproof rolling material
CN106515115A
Anti-aging elastomer SBS modified asphalt waterproof coiled material and preparation method thereof
CN114395927A
Cited By
High-weather-resistance SBS composite modified waterproof coiled material and preparation method thereof
CN121361247A
High weather-resistant SBS composite modified waterproof membrane and its preparation method
CN121361247B